Legal Protection for Land Owners Regarding the Provision of Land Compensation Costs Due to Land Acquisition for Public Interest - Saragih, Joy Zaman Felix; Sitorus, Rolib (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia as an agricultural country, which has a very large area of agricultural land and has the potential for yields to fulfil the needs of the community. The potential is generally such as agricultural products such as rice, corn, sweet potatoes, and various other palawija, and also plantation products such as oil palm, rubber. Various potential results, so that the land has a high quality and price and has a high level (income) of income from the processing of agricultural land and plantations. Ownership of such land by legal subjects, both individuals and legal entities, is inseparable from the reach of government supervision, and can transfer ownership rights to the government if development is carried out in the public interest. The public interest can be in the form of the construction of toll roads, hospitals, and several other public facilities as mandated by UU No. 2 Year 2012. The community will receive compensation for the land that the state has taken, and if they disagree with the nominal amount of compensation, they may file a lawsuit in the District Court in accordance with the land's legal location. The government will first determine the price of the local object when carrying out land acquisition and revocation from the community. The purpose of this research is to discuss the acquisition and revocation of community land rights. The research method used is normative juridical (normative legal reasearch), namely by collecting secondary data consisting of laws and regulations and various sources of literature review. The analytical approach is to determine the fulfilment of rights received by the community in the context of the acquisition and revocation of land rights by the government, as mandated by UU No. 2/2012